Animal welfare with and without consciousness - Dawkins, M (Wiley, 2017)
Despite recent advances in understanding brain function, consciousness – specifically, how the brain gives rise to conscious experiences – remains ‘the hard problem.’ In humans, there are often multiple routes to the same actions, some of them involving conscious experience, others not. Furthermore, differences in brain circuitry make analogies between humans and other animals more difficult than is generally acknowledged. In this essay, I argue that both the study of consciousness itself and the science of animal welfare benefit from facing up to to these difficulties rather than glossing over them. Animal welfare science, although often defining good welfare in term of what animals feel, does not have to be based on assumptions about which species have conscious experiences. Animal welfare (well-being) can be defined objectively in terms of animal health and what animals want. Such a conscious-free definition is readily understandable by people with very different views about animals and yet is practical enough to point to what factual scientific information is needed in any given case. While not precluding conscious awareness in other species, it allows animal welfare science to move forward without having solved the hardest biological problem of all.